Pengaruh Pelatihan dan Motivasi Kerja terhadap Kinerja Pegawai Objek Wisata Danau Situ Tunggilis Desa Situsari Kecamatan Cileungsi Kabupaten Bogor - Turah Slamet; Muhamad Yusuf (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of training and work motivation on employee performance of Lake Situ Tunggilis Tourism Object, Situsari Village, Cileungsi District, Bogor Regency. This research is aimed at employees of Lake Situ Tunggilis Tourism Object, Situsari Village, Cileungsi District, Bogor Regency. The sample used in this study was 30 respondents. In this study, the sampling technique used was saturated sample and data analysis using multiple linear regression analysis. In hypothesis testing, the T test (Partial) and F test (Simultaneous) with the help of the SPSS version 26 application program. The results of multiple linear regression analysis show that the effect of training on employee performance runs positively and significantly. Work motivation also has results that have a positive and significant effect on employee performance. Based on the results of the F test, training and work motivation simultaneously have a positive and significant effect on employee perfomance. The coefficient of determination of influence is 55.6%. Keywords: training and work motivation, tourism object